Super Hybrid Rice Breeding in China: Achievements and Prospects - Cheng, Shi-Hua; Cao, Li-Yong; Zhuang, Jie-Yun; Chen, Shen-Guang; Zhan, Xiao-Deng; Fan, Ye-Yang; Zhu, De-Feng; Min, Shao-Kai (Journal of integrative plant biology, 2007)
Hybrid rice has contributed greatly to the self‐sufficiency of food supply in China. To meet the future demand for rice production, a national program on super rice breeding was established in China in 1996. The corresponding targets, breeding strategies and most significant advances are reviewed in this paper. New plant type models have been modified to adjust to various rice growing regions. In recognition of the importance of applying parents with intermediate subspecies differentiation in increasing F1 yield, medium type parental lines were selected from populations derived from inter‐subspecies crosses with the assistance of DNA markers for subspecies differentiation. Results also indicate that a substantial increase of biomass is the basis for further enhancement of the grain yield potential, and amelioration of leaf characteristics is helpful in increasing the photosynthetic rate. Thirty‐four super hybrid rice varieties have been released commercially, growing in a total area of 13.5 million hm2 and producing 6.7 thousand million kg more rice in 1998‐2005. Although remarkable progress has been made in super hybrid rice breeding in China, selections on the root system and integration of more biotechnological tools remain a great challenge.